Corrigendum to 'Certain geometric properties of the Wright function'. Issue 8 (2nd August 2016) - Mustafa, N.; Prajapat, J.K.
ABSTRACT: In this paper, some significant scientific errors in the paper by J.K. Prajapat entitled 'Certain geometric properties of the Wright function' are corrected.